Ethics in Islam : friendship in the political thought of al-tawhidi and his contemporaries - Al-Sha'ar, Nuha (New York : Routledge, 2015)
'This book offers a critical study of ethical and socio-political thought in the Buyid period'--
'Offering a new reading of Islamic ethical and political thought in the Buyid period'--
Includes bibliographical references (page 227-246) and index.
Keywords: Abu Hayyan al-Tawhidi, Ali ibn Muhammad, -- active 10th century -- Political and social views; Islamic ethics; Friendship -- Political aspects; Buwayhids